Do People Like Mandatory Rules? The Impact of Framing and Phrasing. Issue 4 (12th November 2020) - Zamir, Eyal; Katz, Ori
Abstract : Market regulation has traditionally focused on disclosure duties, yet mounting evidence questions their effectiveness. The efficacy of nudges is similarly doubted, especially when suppliers counter their effects. Consequently, there is growing interest in mandatory regulation of the content of contracts. Previous studies have examined public opinion about nudges but not about mandatory rules. We explore how the formulation of mandatory rules might affect their judged desirability, focusing on the choices: (1) between negative and positive formulation; and (2) between merely establishing substantive mandatory rules and supervising the wording of the contract as well. We also examine laypersons' general attitude toward mandatory rules. We report the results of four studies, conducted with a representative sample of 968 US adults and 795 MTurk master workers. Contrary to our conjecture, we found that subjects generally judged wording rules as more desirable than merely substantive ones, and positive rules as more desirable than negative ones. There also appears to be strong support for pro-customer mandatory rules, even among conservative people. These results arguably legitimize more, and more effective, mandatory rules. They also suggest that the relative paucity of mandatory rules in US law is not due to public opposition to them but to other reasons.